“Great technology, football and...”: Malaysian language learners’ stereotypes about Germany - Nikitina, L.; Mohd Don, Z.; Loh , S.C. (University of São Paulo, 2014)
Abstract: This study focuses on stereotypes about Germany, its culture and people, held by learners of German in a big public university in Malaysia. It examines not only the stereotypical representations of the target language country but also assesses its favourability and salience, which has not been done previously. The findings revealed that the students’ stereotypes about Germany were varied and diverse. Also, they were overwhelmingly positive. The top three salient categories of images about Germany were related to technology, famous personalities – for the most part football players and scientists – and cars. The findings also indicated that very few references had been made to German culture and to its great cultural figures. The results of the present study suggest that students could benefit from a wider and deeper exposure to German culture in the language classroom.